Understanding the relative valuation of research impact: a best–worst scaling experiment of the general public and biomedical and health researchers. Issue 8 (18th August 2016) - Pollitt, Alexandra; Potoglou, Dimitris; Patil, Sunil; Burge, Peter; Guthrie, Susan; King, Suzanne; Wooding, Steven; Wooding, Steven; Grant, Jonathan
Abstract : Objectives: (1) To test the use of best–worst scaling (BWS) experiments in valuing different types of biomedical and health research impact, and (2) to explore how different types of research impact are valued by different stakeholder groups. Design: Survey-based BWS experiment and discrete choice modelling. Setting: The UK. Participants: Current and recent UK Medical Research Council grant holders and a representative sample of the general public recruited from an online panel. Results: In relation to the study's 2 objectives: (1) we demonstrate the application of BWS methodology in the quantitative assessment and valuation of research impact. (2) The general public and researchers provided similar valuations for research impacts such as improved life expectancy, job creation and reduced health costs, but there was less agreement between the groups on other impacts, including commercial capacity development, training and dissemination. Conclusions: This is the second time that a discrete choice experiment has been used to assess how the general public and researchers value different types of research impact, and the first time that BWS has been used to elicit these choices. While the 2 groups value different research impacts in different ways, we note that where they agree, this is generally about matters that are seemingly more important and associated with wider social benefit, rather than impacts occurring within the research system. These findings are a first step in exploring how the beneficiaries and producers of research value different kinds of impact, an important consideration given the growing emphasis on funding and assessing research on the basis of (potential) impact. Future research should refine and replicate both the current study and that of Miller et al in other countries and disciplines.